Bordetella pertussis - Weiss, Alison (Henry Stewart Talks, 2009)
Pertussis: a medical success story and the limits of medical success, Pertussis is the only vaccine-preventable disease that is increasing in incidence in the USA, Pertussis is cyclic, Pertussis vaccine and its efficacy, Vaccine prevents disease not carriage, Immunization does not yield life-long immunity, Human to human transmission by respiratory droplets, Classical whooping cough and chronic coughing disease, Pertussis is two diseases, B. pertussis is a strict human pathogen, Virulence factors of Bordetella pertussis, Pertussis toxin, Adhesins, Composition of acellular pertussis vaccine, Anti-toxin, anti-adherence and bactericidal antibodies, Opsono-phagocytosis, Role of complement in immunity to B. pertussis